"Audacity of opinion: reflections, journeys, musings" - "Singh, Jaswant" (New Delhi, 2012)
The essays are thought-provoking, prescient, and written by one who has an enviable insight into the workings of India's political, defence and economic system. During his long and celebrated career, Jaswant Singh has witnessed India's growth from within, being a part of its chequered political history. The essays touch upon complex issues including the Assam Accord, terrorism in Punjab, India as a secular, socialist republic, the challenges of diplomacy, and the nuclear conundrum. In the section 'Voices of the District', Singh touchingly writes about the acute problems due to scarcity of water, and fodder for cattle; he writes about the peoples' tenacity to fight every adverse situation. The essays are a brilliant expose on the 'state of India', and written in Jaswant Singh's inimitable style laced with wry humour, they are a telling account of the India of today.
Keywords: Politics-India